COOPERATIVISM AND SOLIDARITY ECONOMY: LABOR ORGANIZATION FORMS OF THE COLLECTION IN VITORIA DA CONQUISTA-BA/BRAZIL - Santos, Adma Viana; Carvalhal, Marcelo Dornelis [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The organization of recyclable material collectors cooperatives/associations in addition to income, may mean better working conditions. However, there is still that there are many issues that present themselves as problems concerning the organization of collectors in solidarity economic enterprises. Thus, the aim of this research was to understand the conditions/labor relations present in recycling cooperatives, from the collective organization Cooperative Recycles Conquista in the city of Vitoria da Conquista in Bahia state/Brazil. To this end, interviews were conducted with the members and the leaders of the Recycle Conquest. This research showed that these organizational processes, despite representing a significant improvement of living conditions and work, largely raises vulnerable groups of pickers workers, focusing on economic conditions, poor policies and infrastructure, making it difficult to realize equal with greater autonomy.
Keywords: Cooperatives; Collection of recyclable material; Labor relations